Material Usage of Oil-Palm Empty Fruit Bunch (EFB) in Polymer Composite Systems - Valášek, Petr; Ambarita, Himsar (Manufacturing Technology Journal, 2018)
This paper describes the material use of EFB biomass in the form of composite systems. It describes the tensile characteristics, hardness and wear resistance of polymeric disordered composites epoxy/EFB prepared by vacuum infusion. Electron microscopy was used to describe cellulose EFB fibers and their microstructures. The paper deals with a very simple material when the fibers were not separated from the EFB biomass - EFB biomass was used as it is produced by the processing line. The experiment describes composites with untreated EFB biomass and EFB biomass treated chemically with alkali - 6% aqueous NaOH. Due to the residue of the seed shells and clumps/fiber additions, the cracks initiate and the tensile characteristics decrease up to 46%. Although there have been no significant increases in observed characteristics, this material has some potential in terms of design or in the form of insulating material. The resulting properties could be enhanced by chemical treatment of the fibers, separation of fibers from the residues of the fruit and preferred fiber orientation.
Keywords: cellulose; tensile strength; renewable resources; natural fibres